(untitled) (Journal of Computational Mathematics, 1984)
In this paper we suggest a second-order fluid in cell (FLIC) method for the one-dimensional unsteady compressible flow problems. The numerical result obtained by the present method is compared with the one obtained with the original FLIC method and the exact solution for a shock tube problem.